2017
DOI: 10.1111/adb.12513
|View full text |Cite
|
Sign up to set email alerts
|

Buprenorphine requires concomitant activation of NOP and MOP receptors to reduce cocaine consumption

Abstract: Buprenorphine’s clinical use is approved for the treatment of heroin addiction; however, evidence supporting its efficacy in cocaine abuse also exists. While for heroin it has been demonstrated that the effect of buprenorphine is mediated by its ability to activate μ-opioid peptide receptor (MOP) receptors, the mechanism through which it attenuates cocaine intake remains elusive. We explored this mechanism using operant models where rodents were trained to chronically self-administer cocaine for 2 hours daily.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
26
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(30 citation statements)
references
References 49 publications
4
26
0
Order By: Relevance
“…Interestingly, this effect was evident only at highest doses of buprenorphine and appeared to be independent from reductions in heroin use. This clinical study replicated evidence from a number of preclinical investigations that systematically demonstrated the efficacy of buprenorphine in attenuating cocaine selfadministration in rats and monkeys and humans (Lukas et al, 1995;Montoya et al, 2004;Sorge et al, 2005;Sorge & Stewart, 2006;Kallupi et al, 2018). In some circumstances, the "therapeutic" effect of buprenorphine on cocaine intake was attenuated by administration of naltrexone (Mello et al, 1993;Wee et al, 2012).…”
Section: The N/ofq System: Coactivation Of Nop and Mop Receptorssupporting
confidence: 68%
See 1 more Smart Citation
“…Interestingly, this effect was evident only at highest doses of buprenorphine and appeared to be independent from reductions in heroin use. This clinical study replicated evidence from a number of preclinical investigations that systematically demonstrated the efficacy of buprenorphine in attenuating cocaine selfadministration in rats and monkeys and humans (Lukas et al, 1995;Montoya et al, 2004;Sorge et al, 2005;Sorge & Stewart, 2006;Kallupi et al, 2018). In some circumstances, the "therapeutic" effect of buprenorphine on cocaine intake was attenuated by administration of naltrexone (Mello et al, 1993;Wee et al, 2012).…”
Section: The N/ofq System: Coactivation Of Nop and Mop Receptorssupporting
confidence: 68%
“…Growing evidence suggests that compounds that co-activate MOP and NOP opioid receptors (Table 4) have potential for the treatment of drug abuse (Ciccocioppo et al, 2007;Toll et al, 2009;Kallupi et al, 2018).…”
Section: The N/ofq System: Coactivation Of Nop and Mop Receptorsmentioning
confidence: 99%
“…Future studies will be necessary to characterize the relative contribution of MOP and NOP receptors to the therapeutic effects of bifunctional MOP/NOP agonists such as BU08028. A role for both receptor systems in the ability of buprenorphine to decrease alcohol self-administration would be consistent with its effects on cocaine self-administration [79]. In the present studies, the acute effects of SCH 221510, a NOP receptor agonist with 217-fold selectivity in binding and 58-fold selectivity in stimulating NOP vs. MOP receptors [11], were similar to those of buprenorphine and BU08028.…”
Section: Discussionsupporting
confidence: 79%
“…Accumulating evidence indicates that a novel strategy that targets both nociceptin/orphanin FQ peptide (NOP) receptors and m-opioid receptors (MORs) may be useful for the treatment of addictions (Khroyan et al, 2007(Khroyan et al, ,2011Toll, 2013;Kallupi et al, 2017a). Buprenorphine is a MOR and NOP receptor partial agonist that has been approved for the treatment of opioid use disorder and has been shown to attenuate the expression of cocaine sensitization in rats (Placenza et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…For example, NOP receptor agonists have been reported to increase the analgesic effects of MOR agonists (Courteix et al, 2004;Cremeans et al, 2012), decrease dopamine release from neurons in brain areas that are associated with the reward pathway (Ikemoto and Panksepp, 1999;Toll, 2013), decrease morphine-induced conditioned place preference (Ciccocioppo et al, 2000), and attenuate the rewarding effects of opioids in rats (Murphy et al, 1999;Rutten et al, 2010). Interestingly, recent results showed that buprenorphine requires concomitant activation of NOP and MOP receptors to reduce cocaine consumption in rats (Kallupi et al, 2017a). This evidence suggests that compounds with high efficacy at MORs and NOP receptors may be useful for the treatment of drug addiction.…”
Section: Introductionmentioning
confidence: 99%